Project Management in The Times of Trust Crisis - Maja JOKIEL; Grzegorz JOKIEL; Robert BOBKIER; Arkadiusz BABCZUK (Communications of International Proceedings, 2024)
Trust is one of the most important factors in organizational development and human interactions. It is not given by definition but rather created through dynamic interactions between individuals and institutions. Therefore, it is essential to acknowledge the existence of varying levels of trust. The aim of this article is to identify tactics and strategies that enable effective and efficient project management during times of trust crisis. Project / Methodology / Approach The authors have conducted a literature review of project management in a trust deficit situation. They have also presented case studies that illustrate the use of necessary techniques in projects at risk due to low trust conditions among stakeholders. The result of this research is a list of required actions (tactics and strategies), that can be employed in projects at risk to enhance the working conditions of managers and contractors. The uniqueness of this research paper is highlighted by the scarcity of dedicated articles in general, in which other authors aim to assist practitioners in managing trust crisis in their projects. Most research papers focus on the positive role of trust in organizations and projects, or how to build this trust. Meanwhile, projects are also conducted in unfavorable conditions, including a crisis of confidence. Therefore, methods and supporting tools are essential to support project managers and contractors in handling different situations, which constitute the primary value of this research paper.
Keywords: trust crisis; project management; causes of project failure